Sufiks Pemarkah Kanji Profesi dalam Bahasa Jepang - Mardianingsih, Benardia Sucisakti; Haryono; Suryadi, Yudi (Universitas Negeri Jakarta, 2020)
This research aims to describe the meaning of suffixes attached to kanji profession inJapanese which have different suffixes but the same meaning. Theories used in thisresearch are morphology and semantics. This research is a qualitative research. The datacollection technique used in this research is literature study. The data analysis techniqueused is the determining element. The data in this research are in the form of kanjiprofession which have the same meaning but different suffixes. Data collected in the formof kanji profession means doctors, teachers, writers and painters. The data source used isdictionary entitled Japanese dictionary by Pristian Wulanita (Team I-Smart University).The result of this research describes the different meaning of the data collected and 医師ishi is used in more formal situation than 医者isha. 医家ika is an ancient vocabularywhich shows that the profession of doctor is the hereditary from his family. 教 師 kyoushiis used not only for a teacher who teaches certain subjects in school, but also can used inother teaching contexts. 教員kyouin means a teacher who educates students at school. 作家sakka becomes more specific as a novelist and 作 者 sakusha is a writer of more generalworks of art such as manga, anime, picture books, drama scripts. 画 家 gaka has thespecific meaning of a painter, while 画師 eshi 絵師 eshi means an illustrator.